Infant feeding practices in Bhaktapur, Nepal: a cross-sectional, health facility based survey - Ulak Manjeswori; Chandyo Ram K; Mellander Lotta; Shrestha Prakash S; Strand Tor A (BMC, 2012)
Abstract Background Promotion of proper breastfeeding practices for the first six months of life is the most cost-effective intervention for reducing childhood morbidity and mortality. However, the adherence to breastfeeding recommendations in many developing countries is not satisfactory. The aims of the study were to determine breastfeeding and infant feeding patterns at nine months of age and to assess factors influencing exclusive breastfeeding practices. Methods In Bhaktapur, Nepal, we carried out a cross-sectional survey of 325 infants who came for measles vaccination at the age of nine months. Mothers were interviewed on details regarding feeding of their child and health since birth. Results Three quarters of all mothers reported that they did not receive any information on breastfeeding during the antenatal visit. Two hundred and ninety five (91%) mothers gave colostrum and 185 (57%) initiated breastfeeding within one hour of delivery. The prevalence of exclusively breastfeeding at 1, 3 and 6 months were 240 (74%), 78 (24%) and 29 (9%), and partial feeding was initiated in 49 (15%), 124 (38%) and 257 (79%) babies, respectively. The main reason, according to the mother, for introducing other foods before six months of age was insufficient breast milk. In logistic regression analyses, mother's knowledge on how long child should be given only breast milk and not living in joint families were associated positively with exclusive or predominant breastfeeding for four months or beyond. Conclusions Despite the high proportion of mothers who initiated breastfeeding immediately after birth, continuation of exclusive breastfeeding for up to six months was not common. Very few mothers received any information on breastfeeding during the antenatal visit, indicating a need for counseling on exclusive breastfeeding. Possible options for this counseling could be during antenatal visits and at regular clinic visits for vaccination.